Financial Implications of the Emergency Medicine Interview Process. Issue 1 (January 2017) - Van Dermark, Jeffrey Todd; Wald, David A.; Corker, John Robert; Reid, David Godley
Abstract: Background: Emergency medicine (EM) residency interviews are an important, yet costly process for programs and applicants. The total economic burden of the EM interviewing process is previously unstudied. Graduate medical education funding and student finances are both fragile shifting sources, which appear to fund most of these economic expenditures. Objectives: The total economic impact of the EM interview season is unknown. This study sought to calculate total dollars spent by EM residency programs and senior medical students (M4) during interview season. Potential solutions for reducing this burden will be outlined. Methods: Institutional review board–approved, piloted e‐mail surveys were sent to accredited (Accreditation Council for Graduate Medical Education [ACGME] and American Osteopathic Association [AOA]) EM program directors (PDs) and M4 student members of EMRA. PDs were queried after the 2014–2015 interview season. PDs questions included demographics, estimated faculty, and resident and administrative time used, along with dollars spent during the 2014–2015 interview season. M4 questions included demographics and dollars spent during the 2015–2016 season. Results were reported using descriptive statistics. Financial data for EM programs were calculated with academic EM faculty, resident, and administrative assistant salaries along with reported hours used during the interview season. Results: A total of 82 of 223 EM PDs completed the survey, reporting an mean annual cost of $210, 649.04 per program to review, screen, and interview applicants based on time spent by faculty, resident, and administrative assistants. A total of 84.6% of EM program costs were due to faculty hours. A total of 180 of 1, 425 EM‐bound M4 students completed the survey, reporting a mean annual estimate of US$5, 065.44 per student to apply and interview. Seventy‐two percent of estimated costs were due to airfare and lodging. Loans and credit cards were the top two methods of payments of these interview costs by students. Extrapolating the cost of EM personnel with hours spent, the economic burden of an interview season for EM programs is approximately US$46, 974, 735.92. M4 students spent US$19, 724, 823.40 for application fees and interview‐related expenses. Conclusions: Emergency medicine residency programs and applicants appear to spend over US$66 million per cycle on the interview process. EM residency programs may save resources by reducing faculty hours associated with the interview process and leveraging administrative and resident resources. Creation of regional or national fixed interview locations may also be appropriate. Applicants may reduce travel costs by participating in video interviews, reducing program applications, and attending regionalized interview days. A full conversation among all specialties and organized medicine needs to take place to reform the systems in place to reduce the economic burden on students and residency programs.